Boundary Controllability of Delay Differential Systems of Fractional Order with Nonlocal Condition - Kumar, Kamalendra; Kumar, Rakesh (Journal of Applied Nonlinear Dynamics, 2026)
Sufficient conditions for boundary controllability of time varying delay differential systems of fractional order with nonlocal condition in Banach space are established. The results are obtained by using fixed point theorems. An example is provided to illustrate our results.